Active for Life: A Work-based Physical Activity Program - Beverly B. Green, MD, MPH; Allen Cheadle, PhD; Adam S. Pellegrini; Jeffrey R. Harris, MD, MPH, MBA (Centers for Disease Control and Prevention, 2007)
BackgroundThe American Cancer Society's Active for Life is a worksite wellness program that encourages employees to be physically active. This paper reports the experience of implementing Active for Life in a worksite setting and its longer-term impact on physical activity.ContextThe Active for Life intervention was provided to employees at Group Health Cooperative, a nonprofit health care system in the Pacific Northwest with 9800 employees.MethodsPosters, newsletters, health fairs, and site captains promoted enrollment in Active for Life. Interventions included goal-setting, self-monitoring, incentives, and team competition. Preprogram and postprogram changes in physical activity were assessed at baseline, 10 weeks, and 6 months.ConsequencesActive for Life was offered to 3624 employees, and 1167 (32%) enrolled; 565 (48%) completed all three surveys. At 10 weeks, all physical activity measures increased significantly. The proportion of employees meeting the guideline of the Centers for Disease and Control and Prevention for physical activity increased from 34% to 48% (P < .01). At the 6-month follow-up, the frequency of exercising enough to work up a sweat (P < .01) remained significantly increased, but other measures of physical activity declined toward baseline.InterpretationA 10-week worksite program implemented at multiple facilities increased physical activity by the end of the intervention, but these changes were not sustained over time. Future interventions might include extending the length of the program, repeating the program, or adding larger economic incentives over time. Any such alternative models should be carefully evaluated, using a randomized design if possible.